PENGARUH BELANJA MODAL DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI PROVINSI DI INDONESIA 2009-2012 - Azwardi Azwardi (Jurnal Ekonomi Pembangunan, 2013)
This research was aimed to know the influence of capital expenditure and labor on Indonesian’s provinces' economic growth.  The method of analysis that used in this research is pooling regression. This research used panel data which collected from Statistics Indonesia Finance Ministry from 2009 until 2012 include 33 provinces in Indonesia. The research result showed that the variables capital expenditures that had positive influence but labor had a negative influence on Indonesian’s provinces economics growth. Keywords: Capital Expenditure, Labor, Province’s Economic Growth